Frequency and Clinical Characteristics of Tympanic Membrane Perforation Outpatients at Dr. Hasan Sadikin General Hospital in 2011â2013 - M., Veronika Ratih; Mahdiani, Sally; Dwiyatnaningrum, Fenny (Althea Medical Journal, 2016)
Background: Tympanic membrane perforation is a hearing problem that has become a health problem in the society. In Indonesia, there are only a few studies regarding tympanic membrane perforation. This study was aimed to observe the frequency and clinical characteristics of tympanic membrane perforation patients.Methods: This was a descriptive study performed from August to September 2014. The data was taken retrospectively from medical records of tympanic membrane perforation patients at Dr. Hasan Sadikin General Hospital from January 2011 to December 2013.Results: Of 579 tympanic perforation patients, there were only 214 medical records met the inclusion criteria. The frequency of tympanic membrane perforation patients increased in 2011 it was 28%, in 2013 it was 37.6%. The number of male patients (53.3%) was higher than female patientsâ. Most patients were in productive age (83.2%). Most patients came with the chief complaint of discharge from ear (36.4%) and the most common etiology was infection (84.1%). Otological examination showed that most patients had unilateral perforation (73.8%). Based on the size of perforation, central perforation (52.3%) was the most common otological finding. From audiogram, most patients had conductive hearing loss (41.5%) with moderate degree of hearing loss (30.4%). Most patients were treated by medications (64.5%).Conclusions: The frequency of tympanic membrane steadily increases with clinical characteristic mostly in male patients in productive age admitted with chieft complain of discharge of ear. The most common etiology is infection. Majority of patients have unilateral central perforation that cause conductive hearing lost. [AMJ.2016;3(1):43â8]Â DOI:Â 10.15850/amj.v3n1.702